Supplementing media with NAD+ precursors enhances the in vitro maturation of porcine oocytes - Charley-Lea POLLARD; Zamira GIBB; Azelle HAWDON; Aleona SWEGEN; Christopher G. GRUPEN (The Journal of Reproduction and Development, 2021)
In vitro maturation (IVM) is an important reproductive technology used to produce embryos in vitro. However, the developmental potential of oocytes sourced for IVM is markedly lower than those matured in vivo. Previously, NAD+-elevating treatments have improved oocyte quality and embryo development in cattle and mice, suggesting that NAD+ is important during oocyte maturation. The aim of this study was to examine the effects of nicotinic acid (NA), nicotinamide (NAM) and nicotinamide mononucleotide (NMN) on oocyte maturation and subsequent embryo development. Porcine oocytes from small antral follicles were matured for 44 h in a defined maturation medium supplemented with NA, NAM and resveratrol or NMN. Mature oocytes were artificially activated and presumptive zygotes cultured for 7 days. Additionally, oocytes were matured without treatment then cultured for 7 days with NMN. Supplementing the IVM medium with NA improved maturation and blastocyst formation while NAM supplementation improved cleavage rates compared with untreated controls. Supplementing the IVM or embryo culture media with NMN had no effect on maturation or embryo development. The results show that supplementing the maturation medium with NA and NAM improved maturation and developmental potential of porcine oocytes.